2021
DOI: 10.1037/dev0001191
|View full text |Cite
|
Sign up to set email alerts
|

Moral duty and equalization concerns motivate children’s third-party punishment.

Abstract: Although children enact third-party punishment, at least in response to harm and fairness violations, much remains unknown about this behavior. We investigated the tendency to make the punishment fit the crime in terms of moral domain; developmental patterns across moral domains; the effects of audience and descriptive norm violations; and enjoyment of inflicting punishment. We tested 5-to 11-year-olds in the United Kingdom (N = 152 across two experiments, 55 girls and 97 boys, predominantly White and middlecl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 75 publications
2
7
1
Order By: Relevance
“…'s (2008) findings about the negative effect of punishment-induced rumination on adults' affective states, we expected that children's punishment enjoyment would decrease across time. Since it has been previously demonstrated that British children's emotional experience of punishing was on average neither positive nor negative when measured at the end of the experiment (Arini et al, 2021), we predicted we would find comparable results also in the current study at the same time point. However, we did not formulate any specific prediction for the temporal pattern compensation enjoyment would follow.…”
Section: Affective States Induced By Third-party Interventionssupporting
confidence: 77%
See 3 more Smart Citations
“…'s (2008) findings about the negative effect of punishment-induced rumination on adults' affective states, we expected that children's punishment enjoyment would decrease across time. Since it has been previously demonstrated that British children's emotional experience of punishing was on average neither positive nor negative when measured at the end of the experiment (Arini et al, 2021), we predicted we would find comparable results also in the current study at the same time point. However, we did not formulate any specific prediction for the temporal pattern compensation enjoyment would follow.…”
Section: Affective States Induced By Third-party Interventionssupporting
confidence: 77%
“…We were less confident in making predictions about the effect of inequity transgressions, given the lack of relevant literature at the time of developing our experiment (contrasting findings were published later, see Lee &Warneken, 2020 and. However, it seemed plausible that children would preferentially endorse compensation in response to inequity, as there is evidence that children are motivated to intervene as third parties by the desire to even out the resource imbalances experienced by victims (Arini et al, 2021). Importantly, in our paradigm resource imbalances could be corrected only via compensation, not punishment.…”
Section: Third-party Interventions: Compensation and Punishmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, enacting punishment can be seen as an emotion regulation strategy to downregulate anger and increase positive emotions. Whereas for adults retaliating against a violator feels satisfying, particularly in second-party situations (de Quervain et al, 2004;Strobel et al, 2011), Arini, Wiggs, andKenward (2021) showed that 7-to 11-year-olds derived only small to medium levels of enjoyment when punishing violators in third-party situations and Marshall et al (2021, supplementary material) found that 5-to 7-year-olds reported more happiness and excitement and less sadness when they did not punish. Social norms as to how one should act on or regulate one's anger might affect whether and how children, adolescents, and adults engage in costly punishment of unfairness.…”
Section: Discussionmentioning
confidence: 99%